2020
DOI: 10.3892/etm.2020.9458
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute pancreatitis severity via determination of serum levels of hsa‑miR‑126‑5p and IL‑6

Abstract: Early assessment of acute pancreatitis (AP) severity is key to its treatment. The present study aimed to explore the role of microRNAs (miRNAs/miRs) combined with inflammatory factors in determining AP severity. For this, serum pro-inflammatory cytokines [tumor necrosis factor (TNF)-α, interleukin (IL)-1, IL-6, IL-8 and IL-10)] and miRNAs [ Homo sapiens (hsa)-miR-548d-5p, hsa-miR-126-5p and hsa-miR-130b-5p] were detected in patients with mild AP (MAP), severe AP (SAP) and recurrent AP (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…A multicenter trial revealed that at a PCT value of 3.8 ng/ml within 96 h after the onset of symptoms, diagnostic sensitivity and specificity for pancreatic necrosis or death were 93% and 79%, respectively 29 . Some studies have also confirmed the potential value of IL‐6 as a prognostic indicator in SAP 30,31 . However, to the best of our knowledge, to date, only 1 study published in 2020 has reported the use of HBP to predict persistent organ failure in AP patients with a specificity of 74%, a sensitivity of 90%, and an AUC of 0.82 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter trial revealed that at a PCT value of 3.8 ng/ml within 96 h after the onset of symptoms, diagnostic sensitivity and specificity for pancreatic necrosis or death were 93% and 79%, respectively 29 . Some studies have also confirmed the potential value of IL‐6 as a prognostic indicator in SAP 30,31 . However, to the best of our knowledge, to date, only 1 study published in 2020 has reported the use of HBP to predict persistent organ failure in AP patients with a specificity of 74%, a sensitivity of 90%, and an AUC of 0.82 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 Some studies have also confirmed the potential value of IL‐6 as a prognostic indicator in SAP. 30 , 31 However, to the best of our knowledge, to date, only 1 study published in 2020 has reported the use of HBP to predict persistent organ failure in AP patients with a specificity of 74%, a sensitivity of 90%, and an AUC of 0.82. 25 Our study revealed that the concentrations of analyzed biomarkers were all significantly higher in deaths than in survivors, suggesting that elevated levels were important risk factors for the development of AP.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, IL-10 production was increased in diabetic BMC when compared with wt BMC (Figure 5 AP [22]. IL-10 is produced by activated T cells such as Treg, Th17, and Th1 cells and macrophages stimulated by bacterial lipopolysaccharides and catecholamines or clearance of apoptotic cells [23].…”
Section: Discussionmentioning
confidence: 79%
“…The severity of AP is associated with increased serum levels of inflammatory cytokines markers including TNF‐α, IL‐1β, IL‐6, IL‐8, and IL‐10 (Chen et al, 2021). Furthermore, IL‐6 is identified as a significant inflammatory cytokine marker in the development of AP (Ćeranić et al, 2020).…”
Section: Discussionmentioning
confidence: 99%